A STUDY OF THE ETIOLOGY AND MANAGEMENT OF POST PARTUM HAEMORRHAGE, AT NISHTAR MEDICAL COLLEGE AND HOSPITAL, MULTAN: Post Partum Haemorrhage - Rafique, Sadaf; Azhar, Tahmina; Ahmed, Zahoor (Pakistan Armed Forces Medical Journal, 2009)
Objectives: The main objectives of present study were to determine the incidence and to identify the various etiological factors of primary post portum hemorrhage (PPH) at Nishter Hospital Multan. We also aimed to review various management options for better outcome and to compare the results with international literature. Study Design: Descriptive study Place and Duration of Study: The study was conducted at the department of obstetric and gynaecology, Nishtar Medical College from October 2000 to September 2001. Patients and Methods: The Study included all the cases presented with the primary admitted at Nishtar Hospital Multan either delivered at Nishtar hospital Multan or outside. All the patients who suffered from PPH were thoroughly interviewed and examined according to the study protocol. Results: A total of 3000 cases admitted in Nishtar Hospital Multan during the study period. Out of these 2100 (70%) were vaginal deliveries and 900 deliveries were caesarean section out of these 117 (3.9%) patients developed PPH. Among the etiological factors most common were; uterine atony 48%, and retained placenta 34%. Most successful management strategy was early use of uterotonic agents (68%). Conclusion: Despite good antenatal care, better health services, early detection of problem, availability of new pharmacological agents and introduction of different surgical options, PPH is still, a major complication of third stage of labour responsible for a high maternal morbidity and mortality.